2013
DOI: 10.1111/joid.12018
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Problem Insufficiency: A Proposed Threshold Concept Emergent in Student Accounts of Memorable Interior Design Educational Experiences

Abstract: Students striving to gain design expertise are likely to face significant barriers, some of which may be specific to a given individual, while others are likely shared among many novices in a discipline. Identifying recurrent patterns of such barriers may inform design pedagogy and indicate larger threshold concepts functioning as portals to disciplinary expertise. In this paper, 38 interior design students in their final required studio, representing three different cohort groups, participated in interviews r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Smith (2013) describes a case where thresholds in design education were identified. Students in the final stage of their education were interviewed regarding their experiences.…”
Section: How Threshold Concepts Can Be Identifiedmentioning
confidence: 99%
“…Smith (2013) describes a case where thresholds in design education were identified. Students in the final stage of their education were interviewed regarding their experiences.…”
Section: How Threshold Concepts Can Be Identifiedmentioning
confidence: 99%
“…The time allocated for studio sessions within the curriculum for different design disciplines has been continuously questioned and criticized (K. M. Smith, 2013Smith, , 2015Yurtkuran & Taneli, 2013). The nature of the studio process forces students to commit their time and effort on semester basis leading to wasting too much time in the studio session itself (Kuhn, 2001;Moore, 2000).…”
Section: Student Workload Distributionmentioning
confidence: 99%
“…Therefore, reflection and collaboration, which are critical aspects of experiential learning in studios (Schön, 1984), are not performed which contributes to less than an effective learning experience (Groat, 2000). According to a study by Smith (2013), interior design students have "overwhelmingly identified that getting studio projects done within the time permitted was one of the major difficulties they faced through-out their undergraduate design education experience." The mismatch between the workload and the time allotted is obvious (K. M. Smith, 2015), which adds to the inefficiency of the traditional design studio format.…”
Section: Student Workload Distributionmentioning
confidence: 99%
See 2 more Smart Citations